Association of GWAS-Reported Variant of Matrix Metalloproteinase 12 Gene with Susceptibility to Ischemic Stroke in Southern Chinese Population - Chen L; Liao K; Zhang Y; Zheng S; He J; Tang H; Wu H; Zhong W; Li S; Li Y (Journal of Inflammation Research)
Linfa Chen,1,2,* Keqi Liao,1,3,* Yutian Zhang,1,3,* Shutao Zheng,1,4 Jiawen He,1,3 Henglei Tang,1,4 Hailing Wu,1,3 Wangtao Zhong,4 Shengnan Li,1,3 You Li1,3 1Guangdong Key Laboratory of Age-Related Cardiac and Cerebral Diseases, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 524001, People’s Republic of China; 2Department of Neurology, Huizhou Third People’s Hospital, Guangzhou Medical University, Huizhou, People’s Republic of China; 3Institute of Neurology, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 524001, People’s Republic of China; 4Department of Neurology, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 524001, People’s Republic of China*These authors contributed equally to this workCorrespondence: You Li; Shengnan Li, Guangdong Key Laboratory of Age-Related Cardiac and Cerebral Diseases, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 524001, People’s Republic of China, Email youli805@163.com; 15625102893@163.comBackground: Accumulating evidence suggests that matrix metalloproteinase (MMP) 12 plays a detrimental role in cerebro-cardiovascular diseases, including ischemic stroke (IS). Previous genome-wide association studies (GWAS) correlated the MMP12 rs660599 variant to IS risk in Europeans. However, this association is yet to be elucidated in the Chinese population. This study aims to assess the genetic predisposition of the MMP12 rs660599 G > A variant with regard to IS risk and short-term outcomes in individuals from Southern China.Methods: The Multiplex SNaPshot assay was used to genotype rs660599 in 1035 IS patients and 1061 age-matched healthy controls. Multivariate logistic regression analyses evaluated the effect of the rs660599 G > A polymorphism on IS susceptibility and short-term outcomes.Results: No significant association was found between the rs660599 G > A polymorphism and IS risk, even in dominant and recessive models. However, a relationship between rs660599 genotypes and diabetic status revealed that carriers of the A allele and the GA/AA genotype were more likely to develop IS. The presence of diabetes exacerbated the larger infarct volumes and elevated serum MMP12 levels seen in IS patients with the rs660599 A allele. The A allele of rs660599 and the GA/AA genotype were both correlated to moderate and severe stroke with poor short-term outcomes.Conclusion: The MMP12 rs660599 polymorphism is associated with a higher incidence of IS in people with diabetes and can serve as a biomarker for assessing the severity of IS and its short-term consequences.Keywords: Ischemic Stroke, Matrix Metalloproteinase 12, polymorphism, risk, short-term outcome